Efficient optical simulation of nano structures in thin-film solar cells - Hornich, Julian; Hager, Georg; Pflaum, Christoph (2018)
Optical simulations are a crucial part in designing and understanding new solar cell devices to help with the transition to more environmentally friendly energy generation. We present a multicore wavefront diamond blocking scheme with multi-dimensional cache block sharing for our hybrid-parallel (MPI+OpenMP) optical solar cell simulation code utilizing the Time Harmonic Inverse Iteration Method (THIIM) to discretize Maxwell's equations. This approach allows to decouple the code from the main memory bandwidth bottleneck and achieves a single node speed-up of up to three compared to an optimal implementation with pure spatial blocking and a multi node speed-up of up to two even with large numbers of compute nodes.
Keywords: Simulation; Time Harmonic InverseIteration Method; Maxwell's Equations; High Performance Computing; Optical Simulation